OS 34-02 CONCENTRATION DEPENDENT EFFECT OF PLASMA RESVERATROL ON CEREBRAL VASODILATOR RESPONSIVENESS (CVR) IN ADULTS WITH TYPE-2 DIABETES MELLITUS (T2DM). (September 2016) - Wong, Rachel; Nealon, Rhenan; Raederstorff, Daniel; Howe, Peter
Abstract : Objective: Having shown that resveratrol consumption can improve flow mediated dilation of the brachial artery, we tested its effects on CVR to hypercapnia in adults with T2DM, a risk population for cerebrovascular disease and cognitive impairments. Design and Method: In a double-blind crossover trial, 34 adults with T2DM consumed 0, 75, 150 and 300 mg of synthetic trans-resveratrol (one dose per week in random order). Before and 1–2 hr after dosing, transcranial Doppler ultrasound was used to assess CVR to a hypercapnic stimulus (breathing Carbogen gas for 3 min) in the middle (MCA) and posterior (PCA) cerebral arteries. Results: Compared with placebo (0 mg), consumption of single doses of resveratrol resulted in significant within-individual improvements of CVR to hypercapnia in both the MCA (75 mg: 13.8 ± 3.5%, P = 0.001; 150 mg: 8.9 ± 3.5%, P = 0.016; 300 mg: 13.7 ± 3.3%, P > 0.001) and the PCA (75 mg: 13.2 ± 4.5%, P = 0.016). There were no significant differences between doses. Plasma concentrations of total trans-resveratrol following 0, 75, 150 and 300 mg doses were 0, 351 ± 43, 688 ± 84 and 1241 ± 147 ng/mL respectively. Within individuals, plasma resveratrol levels predicted treatment changes in CVR to hypercapnia in the MCA (r = 0.296, P = 0.001) but not in the PCA (r = 0.210; P = 0.081). Conclusions: This study provides the first evidence that resveratrol can improve endothelial vasodilator function in cerebral vessels in adults with T2DM. Although the extent of benefit correlated with plasma resveratrol concentration, maximum improvement (30%) was achieved with the lowest dose used (75 mg). Impaired cerebral vasodilator function has been reported as an independent risk factor for stroke and transient ischaemic attack. Therefore these results justify evaluating the potential for chronic resveratrol supplementation to improve cerebrovascular function in T2DM and other populations at heightened risk of cerebrovascular disease and associated pathologies, including accelerated cognitive decline. Moreover they indicate that benefits may be achievable with modest doses of resveratrol.